Metasurface-enabled polarization-independent LCoS spatial light modulator for 4K resolution and beyond - Zhaoxiang Zhu; Yuanhui Wen; Jiaqi Li; Yujie Chen; Zenghui Peng; Jianxiong Li; Lei Zhu; Yunfei Wu; Lidan Zhou; Lin Liu; Liangjia Zong; Siyuan Yu (Light: Science & Applications, 2023)
Abstract With the distinct advantages of high resolution, small pixel size, and multi-level pure phase modulation, liquid crystal on silicon (LCoS) devices afford precise and reconfigurable spatial light modulation that enables versatile applications ranging from micro-displays to optical communications. However, LCoS devices suffer from a long-standing problem of polarization-dependent response in that they only perform phase modulation on one linear polarization of light, and polarization-independent phase modulation—essential for most applications—have had to use complicated polarization-diversity optics. We propose and demonstrate, for the first time, an LCoS device that directly achieves high-performance polarization-independent phase modulation at telecommunication wavelengths with 4K resolution and beyond by embedding a polarization-rotating metasurface between the LCoS backplane and the liquid crystal phase-modulating layer. We verify the device with a number of typical polarization-independent application functions including beam steering, holographical display, and in a key optical switching element - wavelength selective switch (WSS), demonstrating the significant benefits in terms of both configuration simplification and performance improvement.